Botswana's fiscal policy, monetary policy, and exchange rate policy: Three instruments and three targets? - James Clark Leith (The University of Western Ontario, Department of Economics, 2020)
In the decades since Independence Botswana has faced significant macroeconomic challenges. Official institutions set fiscal, monetary, and exchange rate policies in the face of these challenges. This paper identifies a target for each policy, reviews the extent to which each policy has been deployed to achieve its assigned target, and the degree of its success in doing so. Recognising that there are interactions among the policies opens up the possibility of inconsistencies. There have been no egregious inconsistencies, but the failure to take into account the effect of substantial movement of the Rand/SDR exchange rate on prices in Botswana has created a potential policy trilemma.
Keywords: E5; E6; 330; Botswana; Policies; Fiscal; Monetary; Exchange Rate